Peningkatan Pemahaman Konseptual Mahasiswa pada Materi Partikel dalam Kotak Tiga Dimensi melalui Simulasi Schrödinger 3D Berbasis Web - Ines Julwana Telaumbanua; Rut Walle Lisna Telaumbanua; Cantika Maria W Seran; Howard Situmorang; Dewi Wulandari; Yuni Warty (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the improvement of students’ conceptual understanding of energy and wave functions in a three-dimensional particle-in-a-box system through the use of a web-based Schrödinger 3D simulation. This research employed a quantitative approach with a one-group pretest–posttest design involving 20 physics students. The instrument used was a conceptual understanding test administered in the form of pretest and posttest. Data were analyzed using descriptive quantitative analysis and the Normalized Gain calculation. The results showed a significant improvement in students’ understanding. The average pretest score of 5.9 (39.3%) increased to 14 (93.3%) in the posttest. The N-Gain value of 0.89 was categorized as high, indicating that the web-based simulation is highly effective in enhancing students’ conceptual understanding. Based on questionnaire responses, the simulation was found to effectively visualize abstract concepts, increase learning engagement, and facilitate understanding of the relationship between energy, wave functions, and quantum numbers. However, several limitations were identified, particularly in the deeper understanding of wave functions and the need for further feature development. Therefore, the use of a web-based Schrödinger 3D simulation can serve as an effective alternative learning medium to improve students’ conceptual understanding in abstract quantum mechanics topics.